2011
DOI: 10.1007/s10047-011-0622-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of symptom pattern and prevalence before and up to 6 months after implantation of a left ventricular assist device

Abstract: Despite increased use of left ventricular assist devices (LVAD) in patients with advanced or end-stage heart failure; little is known about the reoccurrence of common heart failure symptoms (e.g., fatigue) after LVAD implantation. The objective of this study was to investigate the prevalence and pattern of selected heart failure symptoms and identify changes in symptom patterns before and up to 6 months after LVAD implantation. We used self-report questionnaires to collect data from patients (n = 12) and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…QOL was negatively correlated with sleepiness and positively correlated with daytime function. (42) Sleepiness was found to improve from baseline (1 month post-implantation) to time 2 (6 months), though LVAD patients were still more sleepy at 6 months post-implantation than the age-adjusted norms. Sleep disturbance has been directly related to symptoms of cardiopulmonary congestion and pain in heart failure patients.…”
Section: Interventions To Improve Functional Statusmentioning
confidence: 85%
See 1 more Smart Citation
“…QOL was negatively correlated with sleepiness and positively correlated with daytime function. (42) Sleepiness was found to improve from baseline (1 month post-implantation) to time 2 (6 months), though LVAD patients were still more sleepy at 6 months post-implantation than the age-adjusted norms. Sleep disturbance has been directly related to symptoms of cardiopulmonary congestion and pain in heart failure patients.…”
Section: Interventions To Improve Functional Statusmentioning
confidence: 85%
“…Individuals living with LVAD struggled after discharge with bathing independently, interrupted sleep and returning to pleasurable and meaningful activities including sexual intercourse and driving, which negatively affected both functional status and QOL. (4247) These findings suggest a need to further explore the specific stressors that cause functional limitations and trouble LVAD patients.…”
Section: Interventions To Improve Functional Statusmentioning
confidence: 99%
“…3840 BTT patients struggle with the uncertainties of donor organ availability and the possibility of dying awaiting transplantation. 40 Psychiatric conditions may be even more pronounced in DT patients—they have no hope of transplantation and must indefinitely comply with a complex medical regimen, including the technically difficult task of caring for the device.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that patients had improved their health status, anxiety, and depression in the first few months after LVAD implantation and that those scores of patients receiving LVAD therapy were still below for physical, social, and emotional functioning compared with transplant recipients. After Brouwer's study, some studies [28,29] found decreasing of anxiety/depression after introducing LVADs, but two studies [30,31], whose sample size were about 10, did not found the significant improvement in anxiety and depression. Higher scores on anxiety/ depression over time were associated with poor health status [32] and rehospitalization [33].…”
Section: Brouwers Et Al Reviewed Systematically 16 Quantitative Studmentioning
confidence: 99%